PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA TENTANG MEMECAHKAN SOAL CERITA MATEMATIKA MELALUI MODEL COOPERATIVE LEARNING SISWA KELAS V SDN PLERET KIDUL, PANJATAN. - Deri Putra Satriawan (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research is to describe improve the activity and learning achievement of mathematics solve story question using a cooperative learning model in five grade students of State Primery School ofPleret Kidul Panjatan. The type of research is Classroom Action Research (CAR). The subjects were students in five grade students of State Primery School of Pleret Kidul Panjatan, the number of students 23 people. The object of this study was the increase in activity and learning achievement of solving story questions using of cooperative learning model. Data collection technique used tests to obtain data on student achievement, observation to obtain data on student activity and documentation to strengthen data have been obtained from observation and learning outcomes. Learning achievement data analysis techniques performed by calculating the average value of students who meet KKM observation and analysis of the activity is done by calculating the percentage of aspects of the activity of each student. The validity of the item using the product moment, the reliability problem by using KR-20. The results showed an increase in activity and learning achievement of students. This can be demonstrated by an increase in average pratindakan student activity by 42% and after a given action first cycle increased to 72%. Then the second cycle the average activity of students increased significantly to 88%. Mathematics learning achievement of students also increased, namely on pratindakan there are 8 students or 35% of students have met KKM with an average value of 59. In the first cycle increased with an average value of 69, there were 13 students or 57% of students have met the KKM. In the second cycle a significant increase, the number of students who meet KKM as many as 17 students or 74% of students with an average value of 76. Thus, teachers are advised to apply the model of cooperative learning as an alternative to improve the activity and learning achievement of students.